-5(4y-4)-y=-4(y-4)

Simple and best practice solution for -5(4y-4)-y=-4(y-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(4y-4)-y=-4(y-4) equation:


Simplifying
-5(4y + -4) + -1y = -4(y + -4)

Reorder the terms:
-5(-4 + 4y) + -1y = -4(y + -4)
(-4 * -5 + 4y * -5) + -1y = -4(y + -4)
(20 + -20y) + -1y = -4(y + -4)

Combine like terms: -20y + -1y = -21y
20 + -21y = -4(y + -4)

Reorder the terms:
20 + -21y = -4(-4 + y)
20 + -21y = (-4 * -4 + y * -4)
20 + -21y = (16 + -4y)

Solving
20 + -21y = 16 + -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
20 + -21y + 4y = 16 + -4y + 4y

Combine like terms: -21y + 4y = -17y
20 + -17y = 16 + -4y + 4y

Combine like terms: -4y + 4y = 0
20 + -17y = 16 + 0
20 + -17y = 16

Add '-20' to each side of the equation.
20 + -20 + -17y = 16 + -20

Combine like terms: 20 + -20 = 0
0 + -17y = 16 + -20
-17y = 16 + -20

Combine like terms: 16 + -20 = -4
-17y = -4

Divide each side by '-17'.
y = 0.2352941176

Simplifying
y = 0.2352941176

See similar equations:

| 3(2v-1)=6v-5 | | 3.4-.2(.25)=2.9+1.8(.26) | | 16x-7=137 | | 19-x=19 | | 3(-10x-3)+6x=75 | | 30+2n=-4(5n-2) | | 1.5x^2-5x-4=0 | | -30d+13=18d | | 9x+10=15x-20 | | -8v=60 | | 19-x+x=x | | X(x-8x)=3+x | | 5000-0.3= | | 7.5(4)+40=70 | | 4x+8-3x=92 | | 1.5x^2-5x-6=0 | | 4(2x-1)=32 | | 2xy^2+2=0 | | 42-12=-5s+51 | | 2x^3+33x^2+168x+13=0 | | a^2-(a^2-2)-44=0 | | 7n-10-9m=-13 | | -4(p+1)=-6p | | h-25=8 | | 9+6(x+2)=51 | | 6=m+13 | | N+3n-5=27 | | 12-(-52)=w | | (X+3)(x+9)=2x | | 5.3+1.2=1.94 | | 8(3x-9)+6=4x-3 | | -19-(-50)=a |

Equations solver categories